2019
DOI: 10.1186/s12951-019-0486-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular silica nanocoat formed by layer-by-layer (LBL) self-assembly confers aluminum resistance in root border cells of pea (Pisum sativum)

Abstract: Background Soil acidity (and associated Al toxicity) is a major factor limiting crop production worldwide and threatening global food security. Electrostatic layer-by-layer (LBL) self-assembly provides a convenient and versatile method to form an extracellular silica nanocoat, which possess the ability to protect cell from the damage of physical stress or toxic substances. In this work, we have tested a hypothesis that extracellular silica nanocoat formed by LBL self-assembly will protect root bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Moreover, an interesting study by Feng et al (2019) involving the root border cells of pea, showed that these cells were coated with extracellular silica layers, and therefore were able to adsorb Al on their surfaces preventing Al transport into the cells. Very recently, Xiao et al (2021) reported involvement of Si in decreasing Al accumulation (i.e., non exchangeable Al fraction) in the cell wall of rice root apex by decreasing hemicellulose content, which is a main binding site for Al in the cell wall without affecting its cation exchange capacity.…”
Section: Interactions Of Silicon With Beneficial Elementsmentioning
confidence: 99%
“…Moreover, an interesting study by Feng et al (2019) involving the root border cells of pea, showed that these cells were coated with extracellular silica layers, and therefore were able to adsorb Al on their surfaces preventing Al transport into the cells. Very recently, Xiao et al (2021) reported involvement of Si in decreasing Al accumulation (i.e., non exchangeable Al fraction) in the cell wall of rice root apex by decreasing hemicellulose content, which is a main binding site for Al in the cell wall without affecting its cation exchange capacity.…”
Section: Interactions Of Silicon With Beneficial Elementsmentioning
confidence: 99%
“…Until recently, the only example of Al and Si co-deposition in roots that we are aware of outside the grasses was from Norway spruce ( Hodson and Wilkins, 1991 ) where the phenomenon was observed in the cortical cell walls. One slightly unusual example of Al and Si co-deposition comes from the work of Feng et al (2019) working on the root border cells of pea. They were able to produce an extracellular silica nanocoat formed by layer-by-layer self-assembly on the surface of these cells.…”
Section: Co-deposition Of Aluminium and Siliconmentioning
confidence: 99%
“…When RBCs are generated from the root cap, they build a biological interface between the root surface and soil, and play many functions, such as directly affecting the rhizosphere microecosystem, inhibiting the invasion of the pathogen, reducing root mechanical resistance and protecting the root tip (4,7,8,10,(12)(13)(14)(15)(16)(17)(18). It has been reported that RBCs can quickly release antibiotics, specific enzymes, sugars, and other chemicals to regulate the growth of bacteria, fungi, viruses, and nematodes around the rhizosphere by changing gene expression under stress (18)(19)(20).…”
Section: Functions Of Rbcsmentioning
confidence: 99%
“…Therefore, RBCs are considered to be the front of plant response and defense to stresses. Considering RBCs are easier to be harvested in large quantities and easily purified, they are widely used in studies on Al toxicity (7,8,15,39,52). Of specific interest is pea (Pisum sativum) -Mendel's model genetic material that are capable to produce up to 10,000 RBCs from one root tip (8).…”
Section: The Ideal Plant Single Cell System Of Rbcsmentioning
confidence: 99%